2015
DOI: 10.17221/446/2014-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of anthocyanin degradation and polymeric colour formation in grape juice during heating

Abstract: Danışman G., Arslan E., Toklucu A.K. (2015): Kinetic analysis of anthocyanin degradation and polymeric colour formation in grape juice during heating. Czech J. Food Sci., 33: 103-108.The degradation of total monomeric anthocyanins and changes in the proportion of polymeric colour (% PC) as well as antioxidant capacity of grape juice were studied during heating at 70-90°C. Anthocyanin degradation fitted to a first order reaction model, while the formation of % PC followed zero order reaction kinetics. High corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 23 publications
2
26
0
1
Order By: Relevance
“…Anthocyanin and zein contents increased significantly when the temperature was increased from 30 to 70 ∘ C. A possible explanation for this effect may be that high temperature wileyonlinelibrary.com/jsfa enhanced both the permeation and the solubilization processes, thus improving extraction efficiency. 30 These results are similar to those reported in other studies evaluating the optimal UAE conditions for recovering anthocyanins and proteins from purple sweet potatoes 26,31 and blackberries. 24 Therefore, 50-70 ∘ C was chosen as the extraction temperature for subsequent optimization.…”
Section: Effect Of Ultrasound Temperaturesupporting
confidence: 90%
“…Anthocyanin and zein contents increased significantly when the temperature was increased from 30 to 70 ∘ C. A possible explanation for this effect may be that high temperature wileyonlinelibrary.com/jsfa enhanced both the permeation and the solubilization processes, thus improving extraction efficiency. 30 These results are similar to those reported in other studies evaluating the optimal UAE conditions for recovering anthocyanins and proteins from purple sweet potatoes 26,31 and blackberries. 24 Therefore, 50-70 ∘ C was chosen as the extraction temperature for subsequent optimization.…”
Section: Effect Of Ultrasound Temperaturesupporting
confidence: 90%
“…In terms of polymeric anthocyanin content, after 4 weeks, dried extracts stored at room temperature were polymerized approximately 5 times faster than the dried extracts stored at 45 • C (Figure 15). In addition, it was revealed that polymerization percentages of dried extracts stored at warm temperature were higher than those of dried extracts at room temperature, suggesting that high temperature accelerated the polymerization of the extracts in accordance with van 't Hoff laws and Arrheneus equation [21]. From the graph, it was also indicated that the effect of citric acid concentration was more striking in dried extracts stored at 45 • C than samples stored at room temperature.…”
Section: Stability and Antioxidant Evaluation Of The Dried Extract Frmentioning
confidence: 77%
“…Higher temperature might result in deactivation of the enzymes resulting in reduced catalytic activity [91]. In addition; higher temperature causes thermal degradation of anthocyanins [92]. Further, excess of water retards the enzymatic process due to the formation of an interface that prevents the solvent dispersion into the substrate [93,94].…”
Section: Extraction Of Anthocyaninsmentioning
confidence: 99%